Marrying multicomponent reactions and aggregation-induced emission (AIE): new directions for fluorescent nanoprobes. Issue 37 (1st September 2017) - Long, Zi; Mao, Liucheng; Liu, Meiying; Wan, Qing; Wan, Yiqun; Zhang, Xiaoyong; Wei, Yen
Abstract : Recent development and progress for fabrication and applications of aggregation-induced emission polymers through multicomponent reactions have been summarized in this review. Abstract : Aggregation-induced emission (AIE)-active polymers have emerged as one of the most interesting functional polymers due to their unique optical properties and have been explored for various applications especially in biomedical fields. The fabrication of multifunctional AIE-active polymers through a facile and effective strategy plays a central role in realizing their biomedical applications. Multicomponent reactions (MCRs) have been carried out on a platform of aggregation-induced emission (AIE) to construct these AIE-active block polymers recently. Compared to traditional stepwise methods or post-modifications, "one pot" MCRs exhibited distinct advantages such as high efficiency, short reaction times and atom economy. A series of unique AIE-active polymers have been successfully prepared through "one pot" MCRs and utilised in biomedical applications owing to their superior brightness, photostability, biocompatibility and multifunctional potential. In this mini review, recent advances in the "one-pot" synthesis of multifunctional AIE-active polymers through different MCRs, including polycoupling reactions, tandem polymerization, mercaptoacetic acid locking imine reactions and Kabachnik–Fields reactions are summarized. Chemosensors and biological imaging of these AIE-active polymers from MCRs have also been included. We hope this mini review will significantly promote the development of fabrication and applications of AIE-active polymers.